A case of persistent haematospermia secondary to seminal vesicle calculi in an ageing male. (1st October 2020) - Vazirian-Zadeh, Mahmood; Jones, Adam; Phan, Yih Chyn; Mahmalji, Wasim
Abstract: Seminal Vesicle (SV) calculi are a rare pathology. Clinical presentation usually consists of nonspecific perineal pain and haematospermia. Adjuncts to aid diagnosis include US, MRI, and Vesiculography. This rare condition can be treated conservatively, however, surgical options are becoming more advanced with Vesiculoscopy now being the gold standard. Here, we present a case of a SV calculi treated conservatively.